Measures of accessibility incorporating time reliability for an urban rail transit network: A case study in Wuhan, China. (November 2022) - Liu, Jie; He, Mingwei; Schonfeld, Paul M.; Kato, Hironori; Li, Anjun
Abstract: Time Reliability (TR) affects the accessibility of an Urban Rail Transit Network (URTN), which refers to the reachability of destination stations in this paper. However, existing studies do not incorporate TR into accessibility metrics when measuring a URTN's accessibility. Here, the Buffer Time Index (BTI), which is the ratio of extra "buffer" time needed for arriving reliably to the average Travel Time (TT), is used to measure TR. Time-based, cost-based, and timebound-destination-reachability metrics which incorporate TR are proposed to measure the accessibility of a URTN. A Monte Carlo simulation is applied to estimate TR according to the probability distributions of TT components, which overcomes the difficulty of obtaining many passengers' data. The accessibility of Wuhan's URTN during weekday morning peak hours indicates that the metrics which do not consider TR overestimate a URTN's accessibility. The evaluation results can effectively guide decisions on improvements to a URTN's accessibility. The advantage of the measures of accessibility incorporating TR for a URTN is that they not only improve the reasonableness of evaluation but also reflect an aspect of great concern to passengers.